Harzianic acid exerts antimicrobial activity against Gram-positive bacteria and targets the cell membrane - Ouyang, Xudong; Hoeksma, Jelmer; Beenker, Wouter A.G.; van der Beek, Samantha; den Hertog, Jeroen (Frontiers in Microbiology, 2024)
The thermophilic fungus Oidiodendron flavum is a saprobe that is commonly isolated from soil. Here, we identified a Gram-positive bacteria-selective antimicrobial secondary metabolite from this fungal species, harzianic acid (HA). Using Bacillus subtilis strain 168 combined with dynamic bacterial morphology imaging, we found that HA targeted the cell membrane. To further study the antimicrobial activity of HA, we isolated an HA-resistant strain, Bacillus subtilis strain M9015, and discovered that the mutant had more translucent colonies than the wild type strain, showed cross resistance to rifampin, and harbored five mutations in the coding region of four distinct genes. Further analysis of these genes indicated that the mutation in atpE might be responsible for the translucency of the colonies, and mutation in mdtR for resistance to both HA and rifampin. We conclude that HA is an antimicrobial agent against Gram-positive bacteria that targets the cell membrane.